Microbial degradation and assimilation of veratric acid in oxic and anoxic groundwaters - Lazar, Cassandre Sara; Schwab, Valérie F.; Ueberschaar, Nico; Pohnert, Georg; Trumbore, Susan; Küsel, Kirsten (Frontiers in Microbiology, 2023)
Microbial communities are key players in groundwater ecosystems. In this dark environment, heterotrophic microbes rely on biomass produced by the activity of lithoautotrophs, or on degradation of organic matter seeping from the surface. Most studies on bacterial diversity in groundwater habitats are based on 16S gene sequencing, and full genome reconstructions showing potential metabolic pathways used in these habitats. However, molecular-based studies do not allow to assess population dynamics overtime, nor the assimilation of specific compounds and their biochemical transformation by microbial communities. Therefore, in this study, we combined DNA-, phospholipid fatty acid-, and metabolomic-stable isotope probing, to target and identify heterotrophic bacteria in the groundwater setting of the Hainich Critical Zone Exploratory (CZE), focusing on 2 aquifers with different physico-chemical conditions (oxic and anoxic). We incubated groundwater from 4 different wells, using either 13 C-labeled veratric acid (a lignin-derived compound) (single labeling), or a combination of 13 CO2 and D-labeled veratric acid (dual labeling). Our results show that heterotrophic activities dominated all groundwater sites. We identified bacteria with a potential to breakdown veratric acid (Sphingobium or Microbacterium). We observed differences in heterotrophic activities between the oxic and anoxic aquifer, indicating local adaptations of bacterial populations. The dual labelling experiments suggested that the serine pathway is an important carbon assimilation pathway, and that organic matter was an important source of hydrogen in the newly produced lipids. These experiments also yielded different labelled taxa compared to the single 2 This is a provisional file, not the final typeset article labelling experiments, showing that there exists a complex interaction network in the groundwater habitats.